David Mitrany and South-East Europe: The Balkan Key to World Peace - Ashworth, Lucian M. (The Historical Review/La Revue Historique, 2006)
Today David Mitrany is best known for his work on international functionalism, which influenced the development of European integration and the organisation of United Nations specialised agencies. What is often ignored in the West is his work on South-East Europe. During the inter-war period Mitrany studied both the operation of war government and the subsequent peasant revolution in the Balkans. War government demonstrated that political organisation could bridge the gap between social action and private property, while the peasant social revolution showed that the abstract economics associated with both capitalist and Marxist economics was not applicable outside of urban industrial production. It was through his studies of South-East Europe that Mitrany drew many of the lessons and concepts that were to form the foundations of his international theory.